2020
DOI: 10.3389/fbioe.2020.00724
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Tooth-Derived Stem Cells Behavior in a 3D Biomimetic Scaffold for Bone Tissue Engineering Applications

Abstract: Massive amounts of cell are needed for creating tissue engineered 3D constructs, which often requires culture on scaffolds under dynamic conditions to facilitate nutrients and oxygen diffusion. Dynamic cultures are expected to improve cell viability and proliferation rate, when compared to static conditions. However, cells from distinct types and/or tissues sources may respond differently to external stimuli and be incompatible with culture under mechanical shear stress. The first aim of this work was to show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…However, regarding the quantitative PCR results, the HBMSC showed that the OPS-modified particle uptake enhanced the osteogenic gene expression by those cells (osteocalcin). Regarding the OPS signaling, previous work where this molecule was immobilized on collagen/nanohydroxyapatite scaffolds showed the induction of MSCs from different tissue sources to differentiate into an osteoblast phenotype [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regarding the quantitative PCR results, the HBMSC showed that the OPS-modified particle uptake enhanced the osteogenic gene expression by those cells (osteocalcin). Regarding the OPS signaling, previous work where this molecule was immobilized on collagen/nanohydroxyapatite scaffolds showed the induction of MSCs from different tissue sources to differentiate into an osteoblast phenotype [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a CdS QD functionalized with chitosan (Chi) was modified with O-Phospho-L-serine (OPS) that is a component of many proteins, as result of post-translational modifications [ 18 ]. OPS is an important signaling biomolecule present in native bone proteins and has been immobilized on a Collagen-nanohydroxyapatite matrix, showing an increase in MSC osteogenic differentiation, inducing an early pre-osteoblast phenotype, leading to in vitro and in vivo production of bone proteins (OPN) and precipitation of calcium phosphate crystals at the ECM after 4 and 8 weeks after scaffolds’ implantation [ 19 , 20 ]. OPS has also been involved in other tissue biology such as mediating partial inhibition of microglial phagocytosis [ 21 ] and influencing the immune response [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that dynamic conditions not only promoted the proliferation of DFPCs, but also increased osteogenicrelated gene expressions, ALP activity and osteopontin (OPN) deposition compared with static culture conditions. Interestingly, the dynamic conditions exerted distinct effects on DPSCs, including lower ALP activity and OPN secretion [78]. Thus, the effects of different culture conditions on cells from various sources should be explored and chosen wisely according to the final tissue engineering target and clinical application.…”
Section: Dfpcs Differentiate Into Osteogenic Lineage In Vitromentioning
confidence: 99%
“…It was considered as a candidate for artificial organ building. It is reported that dynamic culture conditions enhanced the migration of DFPCs into the inner part of the scaffolds and contribute to higher tissue ingrowth after being implanted subcutaneously in vivo [78]. Moreover, physiological status of DFPCs plays a critical role in osteogenic differentiation, and DFPCs derived from inflammatory environment displayed less hard tissue formation than normal cells [74].…”
Section: Craniofacial Bone Regenerationmentioning
confidence: 99%
“…MSCs are also able to produce immunomodulatory factors, leading to the creation of a regenerative microenvironment. Thanks to these properties, MSCs may play a main role in regenerative medicine, and some clinical studies have demonstrated that MSCs from different sources may have the ability to repair injured tissues, such as bone (Salgado et al, 2020;Gugliandolo et al, 2021) and corneal tissue engineering (Nosrati et al, 2021a), wound healing and muscle (Martínez-Sarrà et al, 2017), cartilage regeneration (Mata et al, 2017;Dang et al, 2021), as well spinal cord injuries (Asadi-Golshan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%